Growth performance, feed utilization and product quality in slaughter size Atlantic salmon (Salmo salar L.) fed a diet with porcine blood meal, poultry oil and salmon oil. (31st December 2012) - Hatlen, B.; Oaland, Ø.; Tvenning, L.; Breck, O.; Jakobsen, J.V.; Skaret, J.
Abstract In a 17‐week experiment with Atlantic salmon (2.3–5.2 kg) in sea cages, a diet containing European animal by‐products and salmon oil (ABP) was compared with a control diet based on fish and plant ingredients, with respect to performance and product quality. Fish fed with the ABP diet had similar growth rates, but slightly improved feed conversion ratio (feed: gain; 1.08 versus 1.14) compared with the control. No differences were seen in fish length, live weight or condition factor. Final body composition was similar and retention of nitrogen and energy did not differ between diets. Higher DPA (C22:5 n‐3) content in the ABP diet apparently inhibited conversion of EPA (C20:5 n‐3) to DPA, resulting in higher EPA retention in muscle and whole body. Muscle and whole body DHA (C22:6 n‐3) level and n‐3 : n‐6 ratio were higher in the ABP group, corresponding with dietary levels. There were no differences in slaughter yield, quality classification, gaping score or fillet texture between diets. The feed with ABP contained less astaxanthin, possibly because of degradation catalyzed by iron in blood meal, and this resulted in lower muscle colour score and astaxanthin concentration (4.6 versus 6.4 mg kg−1). A sensory test did not reveal any differences in odour, flavour, or texture.